“Fanfare for Oduduwa”: Atukwei Okai’s Re-interpretation of a Yoruba Myth - CAPO-CHICHI ZANOU, LAURE CLÉMENCE (My University, 2017)
History has it that an exiled Edo prince from ancient Benin Empire named Ekaladerhan became the first Ooni, that is to say, the first king of Ile Ife. His people deified him after his passing away, and thereupon they invent about him a legend in which he became Oduduwa. However, apart from the Oduduwa of the legend, there was another mythological Oduduwa in Yoruba cosmogony. This latter is a deity; Olodumare, the Yoruba supreme God, ordered him to create the earth at the beginning of times. In fact, the deity Obatala was the first deity asked to do the task of creating a habitat for humanity, but he failed to do so. Therefore, Olodumare called on Oduduwa to do the sacred task of turning water into earth. Atukwei Okai, a Ghanaian poet, wrote a poem he entitled “Fanfare for Oduduwa” to honour this mythological Yoruba divinity. The poet does not concern himself with the legend of the first Ooni of Ile-Ife, the deity’s namesake; instead, he only focuses on the myth. The Ghanaian poet rewrites the Yoruba story of creation and turns it into a sexual encounter between the sea and the spiritual entity, called Oduduwa.
Keywords: Yoruba myth; re-interpretation; eulogy; a mixture of cultures.